A Case of Clitoral Hypertrophy of Unknown Origin. (1st November 2018) - Okaneya, Tetsuya; Onishi, Kiyoshi; Saze, Michio; Iwakura, Kei; Sakuma, Hiroko
Abstract : Clitoral hypertrophy is caused by disorders of sex development and it is observed from birth in most cases. We encountered a patient in whom normal morphology at birth may have acquired deformity and hypertrophy. The patient was a 10-year-old girl with a chief complaint of pudendal deformity. The clitoral hood was enlarged and the clitoris size was 8 x 5 mm on the first examination. Various tests were performed. Sex chromosome or hormonal abnormalities and tumorous lesions were not detected, and the ovaries, uterus, and vagina were normal, indicating that disorders of mullerian development were negative. In surgery, reconstruction of the vulva was performed following the Marberger method. The present case may have been a very rare case of acquired hypertrophy of unknown origin.